SCIENCE PROJECTS FOR INTROVERTED STUDENTS: HOW DO THEY IMPACT SELF-CONFIDENCE? - Muhammad Nizaar; Haifaturrahmah; Nanang Rahman; Nursina (MIMBAR PGSD Undiksha, 2025)
Introverted students often face challenges in project-based learning, particularly in building self-confidence, which is crucial for academic success. This study aimed to improve the self-confidence of introverted elementary school students through specially designed science-based project activities. The project was tailored to encourage active participation among introverted students. A quasi-experimental one-group pretest-posttest design was applied, involving 22 elementary school students. Data collection methods included questionnaires, observation sheets, and documentation. Self-confidence was assessed based on six indicators: optimism, self-efficacy, rationality, objectivity, responsibility, and courage to undertake projects. Data analysis was conducted using a paired sample t-test. The results revealed that science-based project activities significantly enhanced students’ self-confidence (p-value = 0.015). Students showed improved confidence in trying new activities, collaborating in groups, and expressing emotions. These findings indicate that project-based learning can effectively support the emotional and social development of introverted students. Specific tasks included setting time limits, encouraging exploration of new activities, conducting group work, and expressing emotions after learning sessions. This study emphasizes the importance of inclusive learning designs that provide equal opportunities for introverted and extroverted students to collaborate. It recommends adapting traditional science-based projects to align with the unique characteristics of diverse classrooms. Such adjustments enable all students to actively participate and benefit from project-based learning. Overall, the findings highlight the role of project-based learning as an effective strategy to foster self-confidence and holistic development in introverted students, while ensuring equitable participation in collaborative learning environments.